Reconsidering National Plays in Europe (Springer International Publishing, 2018)
This volume frames the concept of a national play. By analysing a number of European case studies, it addresses the following question: Which play could be regarded as a country's national play, and how does it represent its national identity? The chapters provide an in-depth look at plays in eight different countries: Germany (Die Räuber, Friedrich Schiller), Switzerland (Wilhelm Tell, Friedrich Schiller), Hungary (Bánk Bán, József Katona), Sweden (Gustav Vasa, August Strindberg), Norway (Peer Gynt, Henrik Ibsen), the Netherlands (The Good Hope, Herman Heijermans), France (Tartuffe, Molière), and Ireland. This collection is especially relevant at a time of socio-political flux, when national identity and the future of the nation state is being reconsidered.